Routines and Incentives, and Their Influence on Compliance with the Doctrinal Principles of Fisheries Cooperatives - Villasuso Pino Victor; Santos Briones; Ana Laura Bojorquez (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2023)
Fisheries cooperatives play an important role in Mexico, given that they are capable of generating employment, supplying food, stimulating local commerce, and promoting democracy and social integration in the communities where they operate. Fisheries production cooperatives form part of a sector called the social economy. Nevertheless, like all organizations, they face problems in terms of management, worker relations, rule implementation, and continuance over time. The aim of this study is to analyze and identify the degree of influence that exists between the informal constraints of fisheries production cooperatives (specifically in the form of institutional routines and incentives) and compliance with their doctrinal principles. This study uses a non-experimental quantitative, cross-sectional, correlational-explanatory approach. The research methods consisted of the construction of associated indices, descriptive statistics, correlation analysis and multiple linear regression analysis. Three hypotheses were proposed. With regard to H1, the results showed that informal constraints in the form of routines are moderately correlated with the level of compliance with the formal rules. Regarding the results for H2, it was confirmed that informal constraints in the form of incentives are very weakly correlated with the level of compliance with the formal rules. And with regard to H3, based on a joint analysis of the variables, only routines significantly influenced compliance with these doctrinal principles. Based on the above, it was concluded that routines and not incentives are the factors that exert the greatest influence on compliance with the doctrinal principles of cooperatives.